Parenteral Anticoagulation with the Heparinoid Lomoparan (Org 10172) in Patients with Heparin Induced Thrombocytopenia and Thrombosis - Ortel, Thomas L; Gockerman, Jon P; Califf, Robert M; McCann, Richard L; O’Connor, Christopher M; Metzler, Diane M; Greenberg, Charles S (Thrombosis and Haemostasis, 1992)
Progressive thrombocytopenia may develop in as many as 5% of patients receiving heparin anticoagulation. In these patients, the risk of thromboembolic complications as well as continued thrombocytopenia necessitates discontinuation of heparin and initiation of an alternative anticoagulant when indicated. The heparinoid Lomoparan (Org 10172) is a mixture of several nonheparin low molecular weight glycosaminoglycans with proven anticoagulant efficacy that is generally non-reactive with platelets in the presence of plasma from patients with heparin induced thrombocytopenia, whereas standard heparin will induce platelet aggregation. We evaluated the role of heparinoid as a potential alternative anticoagulant in patients with heparin induced thrombocytopenia. During a 6 month period, we identified six patients with heparin induced thrombocytopenia who required an alternative parenteral anticoagulant, four as primary treatment for specific medical problem, and two as anticoagulation during a necessary surgical procedure. Heparinoid was used successfully in both medical and surgical patients requiring parenteral anticoagulation. In no case was there an exacerbation of the thrombocytopenia nor thromboembolic complications while on heparinoid therapy. Three of our patients sustained hemorrhagic complications, predominantly in the post-surgical setting in association with elevated anti-factor Xa levels and additional anticoagulant agents. We feel that these results confirm the utility of heparinoid anticoagulation in a select subset of patients with heparin induced thrombocytopenia who require continued parenteral anticoagulation.